2015
DOI: 10.1175/jhm-d-15-0059.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Hydrological Comparisons between TRMM and GPM Level-3 Products over a Midlatitude Basin: Is Day-1 IMERG a Good Successor for TMPA 3B42V7?

Abstract: The goal of this study is to quantitatively intercompare the standard products of the Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) and its successor, the Global Precipitation Measurement (GPM) mission Integrated Multisatellite Retrievals for GPM (IMERG), with a dense gauge network over the midlatitude Ganjiang River basin in southeast China. In general, direct comparisons of the TMPA 3B42V7, 3B42RT, and GPM Day-1 IMERG estimates with gauge observations over an extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(161 citation statements)
references
References 40 publications
6
152
0
3
Order By: Relevance
“…PDF emphasizes lighter rainfall rates, making it more suitable for evaluating the ability of satellite precipitation to detect light precipitation [14]. The PDF of satellite precipitation shown in Figure 8a was consistent with that of gauge observations for the rainfall rate greater than 0.5 mm/day and tended to underestimate the gauge precipitation in this study.…”
Section: Discussionsupporting
confidence: 78%
“…PDF emphasizes lighter rainfall rates, making it more suitable for evaluating the ability of satellite precipitation to detect light precipitation [14]. The PDF of satellite precipitation shown in Figure 8a was consistent with that of gauge observations for the rainfall rate greater than 0.5 mm/day and tended to underestimate the gauge precipitation in this study.…”
Section: Discussionsupporting
confidence: 78%
“…Tang et al found that GPM IMERG performed well in hydrological modeling simulation in the mid-latitude Ganjiang River basin in southeast China, outperforming its predecessor TRMM 3B42 [40]. W. Qi et al applied GSMap-MVK data to perform discharge simulations in the Biliu basin located in northwestern China, and results showed that GSMap-MVK had a huge advantage over TRMM 3B42 for discharge simulations, especially at the monthly and inter-annual scales [18]. The two studies cited above also found that good discharge simulation depended on the appropriate match between the hydrological model and precipitation product, as a better precipitation product did not necessarily guarantee a better discharge simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for most developing countries, such as China, with insufficient spatial coverage of in-situ data, long time delays for data processing and availability, and the absence of data sharing across disciplines, the application of satellite-derived precipitation data has shown significant advantages. However, the sources of inherent error associated with these products, which stem from indirect physical estimates of rainfall, have not been well understood to date, especially for the latest HRPP grid data, and would have a significant influence on their application [18]. Therefore, it is essential to evaluate their accuracy and error characteristics by comparing them against observations from precipitation gauges before various applications are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies [31][32][33][34][35][36][37] found that, although 3B42V7 and IMERG products effectively capture the spatiotemporal variations of precipitation in different regions around the world, these estimates still contain considerable errors when compared with ground observations. Given that precipitation inputs are among the most dominant uncertainty sources for hydrological models, satellite precipitation products must be bias-corrected when adopted as the input of a hydrological model for streamflow simulations.…”
Section: Bias-correction For Satellite Precipitation Productsmentioning
confidence: 99%